Peningkatan Hasil Belajar dengan Metode PBL pada Materi Menghormati Orang Tua Kelas IV - Yuhanna Paridah; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to overcome the problem of low learning outcomes in Christian Religious Education (PAK) among fourth-grade students at SD Negeri Karanganyar. Observations indicated that the learning process was monotonous due to the predominant use of lecture methods, resulting in decreased student engagement, lack of focus, boredom, and even drowsiness during lessons. These factors contributed to low learning motivation and poor academic performance. To address this, the Problem Based Learning (PBL) model was applied as an alternative method designed to foster active learning, student engagement, and real-life problem-solving skills. This research employed a Classroom Action Research (CAR) design, conducted in two cycles with four stages in each cycle: planning, implementation, evaluation, and reflection. The research subjects were five students from class IV. Data collection techniques included observation sheets, which focused on measuring the “concern” aspect of the Pancasila Student Profile, and written tests to evaluate students’ learning outcomes at the end of each cycle. The data were analyzed using descriptive statistics and percentage analysis. The results showed a significant improvement in students’ concern, which increased from 73.5% in cycle 1 to 85.9% in cycle 2—an increase of 12.4%. Learning outcomes also improved, with the proportion of students in the “Proficient” category rising from 20% to 60%, marking a 7.8% increase. These findings demonstrate that the PBL method is effective in enhancing both students’ character values and academic achievement, particularly on the topic of respecting parents. Therefore, PBL is recommended for use in similar character-based learning contexts.